The Role of Organizational Innovation In The Influence of Organizational Learning and Transformational Leadership on Organizational Performance In The Digital Technology Industry - Agustinus Setyawan; Yuliana Shintia; Alden Nelson (Dinasti Publisher, 2024)
This study aims to determine the role of innovation in the influence of organizational learning and transformational leadership on organizational performance in the digital technology industry. The population of respondents in this study were employees of the digital technology industry. Sampling of respondents was carried out by distributing questionnaires with multivariate data analysis methods, where the number of samples that met the criteria was 386 employees in the digital technology industry. From the research results, there are seven direct relationship hypotheses accepted. Organizational innovation fully mediates the relationship between organizational learning and organizational performance and mediating the relationship between transformational leadership and organizational performance. Future research can focus on social issues and the development of the digital technology industry